Molecular characterization of Der p 10: a diagnostic marker for broad sensitization in house dust mite allergy - Resch, Y. (Clin Exp Allergy, 2011)
BACKGROUND: Tropomyosins represent clinically relevant seafood allergens but the role of mite tropomyosin, Der p 10, in house dust mite (HDM) allergy has not been studied in detail. OBJECTIVE: To express and purify a recombinant Der p 10 with equivalent IgE reactivity as natural Der p 10 and to evaluate its IgE reactivity and allergenic activity in HDM-allergic patients. METHODS: rDer p 10 was expressed in Escherichia coli, purified and characterized by mass spectrometry and circular dichroism. It was tested for IgE reactivity in 1322 HDM-allergic patients. Detailed IgE-reactivity profiles to six HDM allergens (Der p 1, 2, 5, 7, 10, 21) were established for subgroups of Der p 10-positive and -negative patients. The allergenic activity of rDer p 10 was evaluated in basophil degranulation experiments. RESULTS: rDer p 10 is an α-helical protein sharing IgE epitopes with nDer p 10. It is recognized by 15.2% of HDM-allergic patients. Der p 10-negative patients were primarily sensitized to Der p 1 and/or Der p 2, whereas Der p 10-positive patients reacted to several other HDM allergens besides the major allergens (Der p 1, Der p 2) or showed a rather selective Der p 10 reactivity. The allergenic activity of Der p 10 was generally low but patients could be identified who suffered from clinically relevant HDM allergy due to Der p 10 sensitization. CONCLUSION AND CLINICAL RELEVANCE: Der p 10 may be a diagnostic marker for HDM-allergic patients with additional sensitization to allergens other than Der p 1 and Der p 2. Such patients may require attention when allergen-specific immunotherapy is considered.